2015
DOI: 10.2478/aoa-2014-0031
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Soluble Cellouronic Acid Sodium Salt by 4-Acetamide-TEMPO Mediated Oxidation of Ultrasound-Pretreated Parenchyma Cellulose from Bagasse Pith

Abstract: The parenchyma cellulose isolated from bagasse pith was used as an alternative resource for preparation of water-soluble cellouronic acid sodium salt (CAS). The influence of ultrasound treatment on the cellulose was investigated for obtaining CAS by regioselective oxidization using 4-acetamide-TEMPO and NaClO with NaClO2 as a primary oxidant in an aqueous buffer at pH 6.0. The yield, carboxylate content and polymerization degree (DP) of CAS were measured as a function of ultrasonic power, agitating time and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This could be attributed to the difference in microstructures between parenchyma cell cellulose and fibrous cellulose. The microfibrillar cellulose crystals within parenchyma showed a less ordered arrangement than those found in the fibers (Gao et al 2014a). The loose arrangement of cellulose chains in the parenchymal cells was corroborated with the notably lower cell wall density (1.28 vs 1.52 g/cm³) and increased porosity (0.013 vs 0.007 cc/g following chemical pretreatments), in comparison to the fibrous one (Zhang et al 2022b).…”
Section: Resultsmentioning
confidence: 94%
“…This could be attributed to the difference in microstructures between parenchyma cell cellulose and fibrous cellulose. The microfibrillar cellulose crystals within parenchyma showed a less ordered arrangement than those found in the fibers (Gao et al 2014a). The loose arrangement of cellulose chains in the parenchymal cells was corroborated with the notably lower cell wall density (1.28 vs 1.52 g/cm³) and increased porosity (0.013 vs 0.007 cc/g following chemical pretreatments), in comparison to the fibrous one (Zhang et al 2022b).…”
Section: Resultsmentioning
confidence: 94%
“…It is noticed that cellulose microfibrils in the parenchyma cell walls are less uniform in diameter and less aligned than those in fibrous cells [25]. We reported a green ultrasound pretreatment of celluloses from the two different cells in order to improve the selective oxidation for the preparation of water-soluble oxycellulose [26]. The results showed that ultrasonic treatment of parenchyma cellulose (PC) had more effect on its yield than that of fibrous cellulose.…”
Section: Introductionmentioning
confidence: 94%